Why did he do that? Using counterfactuals to study the effect of intentions in extensive form games - Yola Engler; Rudolf Kerschbamer; Lionel Page (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
We investigate the role of intentions in two-player two-stage games. For this purpose we systematically vary the set of opportunity sets the first mover can chose from and study how the second mover reacts not only to opportunities of gains but also of losses created by the choice of the first mover. We find that the possibility of gains for the second mover (generosity) and the risk of losses for the first mover (vulnerability) are important drivers for second mover behavior. On the other hand, efficiency concerns and an aversion against violating trust seem to be far less important motivations. We also find that second movers compare the actual choice of the first mover and the alternative choices that would have been available to him to allocations that involve equal material payoffs.
Keywords: C91; C92; D63; D64; 330; Social Preferences; Other-Regarding Preferences; Intentions; Reciprocity; Trust Game; Experimental Economics; Behavioral Economics